Рыжее братство. Возвращение - Фирсанова Юлия Алексеевна (Юлия Фирсанова с непростой историей, 2011)
Экземпляры: ф.17 (20200828) / Инвентарный номер: 60132 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Ф 62 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-445